Analisis Tingkat Kesehatan Bank Menggunakan Metode Rgec (Risk Profile, Good Corporate Governance, Earnings, dan Capital) pada Bank Umum BUMN Periode 2018-2020 - Muhamad Bayu Nur Rohman (Jurnal Riset Manajemen dan Bisnis, 2021)
Abstract. This study aims to determine the health level of BUMN Commercial Banks from the aspects of Risk Profile, Good Corporate Governance, Earnings, Capital and RGEC as a whole. The author uses 4 sample companies with a time period of 2018-2020. This research uses descriptive quantitative research methods. The data analysis technique used is descriptive analysis with reference to POJK No. 4/POJK.03/2016. The results showed that in terms of the Risk Profile, the NPL ratio of BUMN Commercial Banks for the 2018-2020 period was categorized as "Healthy". From the GCG aspect, it shows that the 2018-2020 period of state-owned commercial banks is categorized as "Healthy". In terms of earnings, it shows that in 2018-2020 the ROA of BUMN Commercial Banks was categorized as “Very Healthy”, and in 2020 it was categorized as “Fairly Healthy”. Furthermore, the 2018-2020 NIM is categorized as "Very Healthy". In terms of capital, it shows that in the 2018-2020 period, state-owned commercial banks were categorized as "Very Healthy". In terms of RGEC as a whole, in 2018-2019 BUMN Commercial Banks were categorized as “Very Healthy”, while in 2020 they were categorized as “Healthy”. Abstrak. Penelitian ini bertujuan untuk mengetahui tingkat kesehatan Bank Umum BUMN dari aspek Risk Profile, Good Corporate Governance, Earnings, Capital dan RGEC secara keseluruhan. Penulis menggunakan 4 sampel perusahaan dengan periode waktu 2018-2020. Penelitian ini menggunakan metode penelitian deskriptif kuantitatif. Teknik analisis data yang digunakan adalah analisis deskriptif dengan acuan POJK No. 4/POJK.03/2016. Hasil penelitian menunjukkan dari segi Risk Profile bahwa rasio NPL Bank Umum BUMN periode 2018-2020 dikategorikan “Sehat. Dari aspek GCG menunjukkan bahwa periode 2018-2020 Bank Umum BUMN dikategorikan “Sehat”. Dari segi earnings menunjukkan bahwa pada tahun 2018-2020 ROA Bank Umum BUMN dikategorikan “Sangat Sehat”, dan di tahun 2020 dikategorikan “Cukup Sehat”. Selanjutnya NIM pada tahun 2018-2020 dikategorikan “Sangat Sehat”. Dari segi capital menunjukkan bahwa pada periode 2018-2020 Bank Umum BUMN dikategorikan “Sangat Sehat”. Dari segi RGEC secara keseluruhan, pada tahun 2018-2019 Bank Umum BUMN dikategorikan “Sangat Sehat”, sedangkan di tahun 2020 dikategorikan “Sehat”.